Fairy Tale Saloon / Mohammad Hambiah... [et al.] - Jauli, Anisah; Dailip, Delna; Md Reduan, Norina; Rahman, Muhammad Raziman; Hambiah, Mohammad (2014)
Fairy Tale is a business that deals with variety fashion of hairstyle industry in Malaysia. From the establishment of Fairy Tale, we come out with The Saloon shop for kids. By walk in to our Saloon shop, customer will be serves with better service and experience wonderful moment once enjoying our services. The name of Fairy Tale is chosen because we are providing a service for the children. For our services, the hairstyle can be choose based on what customer want, various fashion of hairstyle was available for our customer. So, parents can freely choose what style they want for their kids. The location for our shop is at One Borneo Hyper mall, Sepanggar. From the location chosen, we believe that it is a strategic place to attract customers which we are targeting school and a parents. The differences of our services may bringing satisfaction, happiness, and joy to customer. Furthermore, we also come out with other alternatives to serve our customer, where provide a good condition of the saloon shop and the customer service.